THE QUALITY OF LIFE CHILDREN WITH STUNTING AGE 2-4 YEARS AT PARIT MAYOR HEALTH CENTER, EAST PONTIANAK - Jannah, Fisqiyatul (Universitas Tanjungpura, 2021)
Background: Stunting is a form of malnutrition defined as low height-for-age, it is the result of chronic or recurrent undernutrition. Based on WHO in 2019, globally 21.3% or 144 million children under the age of 5 years of age were stunted. In 2019, for West Kalimantan at Pontianak City, East Pontianak has the highest prevalence of stunting at 20.62% with an estimated 1610 children. Stunted children experience a decrease in quality of life, especially in physiological conditions such as cognitive development and also decreased emotions. Purpose: To know the quality of life children with stunting age 2-4 years at Parit Mayor Health Center, East Pontinak. Method: This was an observational descriptive quantitative study. A sample of 50 children under five was selected for this study by total sampling. Result: the study describe children under five who suffered stunting of life using the measurement of PedsQl questionnaire. The result of analysed, from 50 children under five who answered 18 items question show 33 children (66%) having the quality of their life at risk and 11 children under five who answered the 21 items questions show 7 children (63.6%) were also quality of life at risk. Conclusion: In this study could describe that most of children who is suffered stunting have the quality of their life at risk. At health center.